Processus d’intégration de villages périphériques dans le système d’approvisionnement de Bamako - Gwenaëlle Raton (EchoGéo)
The increase in the number of market places on the outskirts of Bamako which supply the city with food allows one to study how villages and new agricultural units are integrated to the urban supply chains. The unequal distribution of market places on the Bamako periphery and the central role they play for local inhabitants leads one to ponder three questions. The first question concerns the policies which influenced the diffusion and normalization of a selling model characterized by weekly markets, locally known as “fairs”. The second question bears on the appropriation of this selling model by peasant communities and on the densification and extension of the resulting network. The third question raises the issue of the sustainability of this selling model, which tends to vary depending on proximity to the city.